Measurement of Tax Progressivity: Comment - Kienzle, Edward C. (American Economic Review, 1980)
In a recent issue of this Review, Daniel contributed an excellent method for deriving a measure of tax progressivity (or regressivity). The Suits S, closely related to Lorenz curve and Gini coefficient analysis, is an ingenious extension of that measurement methodology. It provides a widely applicable summary statistic of the progressivity of a particular tax or tax structure.' demonstrates the mathematical properties of S and applies the index to the U.S. tax structure. He examines 1966 tax data developed by Joseph Pechman and Benjamin Okner, and 1970 tax data developed by Okner (1976) and compares the results for the two years. Economic theory does not provide a definitive answer to tax incidence questions and the subsequent allocation of tax burdens across income classes. Application of legitimate competing theories concerning tax incidence results in different implications for tax progressivity. Therefore, alternative assumptions should be considered when measuring tax progressivity. The purpose of this paper is to examine the results obtained from an application of the Index and Lorenz curves of taxes when an alternative set of assumptions is chosen and to show that S and the Lorenz curves are sensitive to that choice.